Penerapan Penerapan Algoritma Greedy dalam Penentuan Menu Diet Berdasarkan Kandungan Kalori dan Protein - Azzahra, Fathimah (JATISI, 2024)
Weight is a sensitive issue for some people, especially among teenagers, being overweight is often the reason people feel insecure and hate themselves. Many teenagers will go on a diet to achieve the ideal body, but not all of them will be consistent. Many challenges and obstacles cause an inconsistent diet, one of which is the difficulty of counting calories. To solve this problem, a greedy algorithm is applied to determine a diet food menu based on calories and protein using the calorie deficit diet method. Calorie limit calculations are performed using Basal Metabolic Rate (BMR) and activity level. In this problem, the greedy algorithm will minimize calories, maximize protein, and maximize density. The result of applying the greedy algorithm in determining the diet menu is that there are conditions that produce solutions that are not optimal, but the difference in the resulting solutions is not too significant so this algorithm is still possible to solve the problem of constraints on counting calories and managing diet menus.